PERENCANAAN PEMANFAATAN RUANG BERBASIS KONSERVASI MANGROVE DI WILAYAH KEPESISIRAN KABUPATEN DEMAK - , Septiana Fathurrohmah ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The mangrove forests in Indonesia partly have been degraded over time, include mangrove forest in coastal area of Demak Regency. The aims of this study are to identify the existing conditions of mangrove forests, design a mangrove conservation plan, describe land suitability for several non mangrove utilizations, and arrange the space utilizations planning based on the mangrove conservation in coastal area of Demak Regency.The identification of existing conditions includes the analysis of mangrove coverage changes and the mangrove critical stage. Visual interpretation of time series satellite imageries data is used to analyze the mangrove coverage changes. Whereas, the assessment of mangrove critical stage is based on the kinds of landuse, mangrove crown density, and soil resistivity from coast erosion. The mangrove conservation plans are determined by the score and the assessment of the mangrove coverage decrease, the mangrove critical stage ,the existence of shore and river borders, and potential land-use of mangrove. For land suitabilities, the analyses use arithmetic matching. The space utilizations planning based on mangrove conservation is compiled by use the results of land suitability analyses of mangrove and other several sectors to get space utilizations alternatives and matrix of space utilizations interactions as the basis to analyze the interactions and determine the final space utilization. The mangrove coverage in study area were about 1.979,58 Ha (1994), 1.077, 29 Ha (2002), and 1.405,36 Ha (2010). The result of mangrove critical stage analysis shows that about 83,29 % of mangrove forests are categorized as a damaged mangrove area, 12,68% are in a badly damaged stage, and 4,04% can be categorized as a nondamaged mangrove area. The results of mangrove conservation plans are first priority mangrove conservation zone covers 3.058 Ha, second priority mangrove conservation zone covers 1.531,7 Ha, and third priority mangrove conservation zone covers 9.782,5 Ha. In the analyses of land suitability, almost all the study areas can be categorized as a suitable area for port and most of the areas also can be classified in moderate category for aquaculture, industry, and settlement. The result also shows that all of the areas being studied are suitable for agricultural sectors, and almost all of study area are not suitable for tourism. The space utilizations plans based on conservation mangrove include 19.400 Ha of agriculture areas, 9.444 Ha of silvofishery areas (the combination of third mangrove conservation priority area and fishpond), 1.590 Ha of settlement areas, 1.211 Ha of silvofishery areas (the combination of second mangrove conservation priority area and fishpond), 351,7 Ha of the third priority mangrove conservation areas, 166,2 Ha of the second priority mangrove conservation areas, and 40,28 Ha of fishpond areas.